Pruritus may precede abnormal liver function tests in pregnant women with obstetric cholestasis: a longitudinal analysis - Kenyon, Anna P.; Piercy, C. Nelson; Girling, J.; Williamson, C.; Tribe, R.M.; Shennan, A.H. (BJOG : an international journal of obstetrics and gynaecology, 2001)
Obstetric cholestasis is a liver disorder unique to pregnancy, which typically presents with pruritus. However, pruritus is common in pregnancy and the diagnosis of obstetric cholestasis is confirmed by finding abnormal liver function. We report 10 cases in which pruritus occurred before any abnormality in liver function tests (including total serum bile acids) and discuss the implications of this for clinical practice.